Method of low-cycle fatigue test results processing - Mroziński, S.; Lipski, A. (Фізико-хімічна механіка матеріалів, 2012)
There is considered the method of proceeding during elaboration of low-cycle fatigue test results of metals. Presented method enables to determine the material data in various periods of fatigue life. The results obtained with the use of proposed method allow taking into account during fatigue life calculations as the visible changes of cyclic properties of material. The above is of special importance in the case of material characterized by the absence of stabilization period. Подано новий метод аналізу результатів мaлoциклoвих випробувань металів на втому, який дає змогу визначити характеристики матеріалів на різних стадіях втоми. Отримані дані можуть бути використані для розрахунків втомної довговічності елементів конструкцій. Представлен новый метод анализа результатов мaлoциклoвых испытаний металлов на усталость, который позволяет определить характеристики материалов на разных стадиях усталости. Полученные данные могут быть использованы для расчета усталостной долговечности элементов конструкций.